Reforestation and sylvopastoral systems in Sahelian drylands: evaluating return on investment from provisioning ecosystem services, Senegal - Cesaro, Jean-Daniel; Mbaye, Tamsir; Ba, Baba; Ba, Marieme Fall; Delaye, Etienne; Akodewou, Amah; Taugourdeau, Simon (Frontiers in Environmental Science, 2023)
Since the 1960s, droughts have caused significant degradation of Sahelian ecosystems, particularly resulting in a reduction in tree cover. Despite the challenges posed by climate change, the rural Sahelian population continues to depend on natural resources for pastoral livestock farming, which remains a critical source of livelihood. To address this issue of land degradation, Sahelian states and international coalitions are prioritizing efforts to restore pastoral land through reforestation programs. These initiatives aim to enhance ecosystem services, generate new income for the population, and safeguard biodiversity.In practice, however, reforestation has often led to a depletion of resources for communities due to enclosure policies. This paper explores various land management models for reforestation within a pastoral context through provisioning ecosystem services (PES) modeling.This study quantifies the economic potential of PES offered by reforestation programs in Senegal. It employs a quantitative methodology to assess the profitability of these operations from the perspective of pastoral economies. The analysis reveals that the PES benefits of reforestation can significantly enhance the economic potential of sylvo-pastoral productions if resource access is negotiated collaboratively between pastoralists and forestry extension services during reforestation activities and after. From an investment perspective, the economic viability of reforestation operations in drylands is questionable. The findings suggest that when evaluated solely in terms of PES profitability, these programs may not be financially sustainable. The sustainability of these investments would require taking into account supporting and regulating ecosystem services.